2020
DOI: 10.1051/e3sconf/202014204001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starter sources and old fermentation on making nata de whey towards chemical quality

Abstract: Whey cheese is a by-product of traditional or modern cheese-making processes. The yield of each cheesemaking reaches around 83% of the volume of milk used.whey can be processed into nata de whey by adding Acetobacterxylinum. The purpose of this study were to determine the effect of fermentation duration and differences in starter sources on the chemical quality produced by nata de whey. All samples were analyzed for fat, protein, cellulose and reducing sugars. this use study of two factorial randomized block d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
1
0
3
Order By: Relevance
“…showed that the death phase did not occur until the fermentation time is completed. The death phase usually occurs from the 8th day to the 15th day [32]. A reported study showed that the death phase occurred starting on the 16th day of BC production with A. xylinum 0416 grown in HS medium [28].…”
Section: Biomassmentioning
confidence: 99%
“…showed that the death phase did not occur until the fermentation time is completed. The death phase usually occurs from the 8th day to the 15th day [32]. A reported study showed that the death phase occurred starting on the 16th day of BC production with A. xylinum 0416 grown in HS medium [28].…”
Section: Biomassmentioning
confidence: 99%
“…Apabila konsentrasi bakteri terlalu rendah maka kadar air yang dihasilkan semakin tinggi sehingga mengakibatkan kuat tarik membran menjadi lemah (Shobib et al, 2019). Sementara jika konsentrasi bakteri terlalu tinggi serat yang terbentuk makin banyak dan ikatan hidrogen yang terbentuk antar serat semakin kuat (Khusna et al, 2020). Ikatan hidrogen yang kuat akan meningkatkan kuat tarik membran (Mondal, 2015).…”
Section: Persentase Bakteri Yang Digunakanunclassified
“…Selulosa bakteri semakin banyak dihasilkan ketika waktu fermentasi yang diperlukan semakin lama (Aulia et al, 2020). Dengan semakin banyaknya selulosa yang terbentuk maka ikatan hidrogen antar serat semakin kuat (Khusna et al, 2020). Namun pada penelitian Abdelraof et al (2019) proses fermentasi yang dilakukan selama 4 hari dapat menghasilkan selulosa bakteri 2,61g/l.…”
Section: Kondisi Fermentasiunclassified
“…Nata de Soya merupakan produk dengan kandungan air yang tinggi, sehingga sangat bermanfaat untuk metabolisme tubuh [4]. Semua sisa pembakaran dalam tubuh manusia yang tidak terserap sempurna akan diikat oleh air kemudian dikeluarkan lewat alat pencernaan sebagai fases [5]. Fungsi air antara lain berperan sebagai pelarut, membuang sisa metabolisme, serta mengontrol suhu tubuh dan volume sel [6].…”
Section: Pendahuluanunclassified